Learning and teaching with literary archives. Issue 1 (November 2018) - Dean, Heather
Abstract : Archives, and particularly literary archives, have a value in learning and teaching in postsecondary education. This paper explores trends in education and the profession inspiring archivists and educators to incorporate archives into the curriculum. A call for active learning, and recognition of the importance of hands-on experiences with primary source materials, has contributed to a unique and unprecedented opportunity to connect students with rare and unique materials. The growth of book history as a discipline has also provided impetus for collections-based curriculum and rooting coursework within cultural heritage institutions. This paper focuses specifically on literary archives and seeks to articulate both the value this material brings to the classroom as well as provide concrete ideas for exercises.